Lipid peroxidation and osmotic fragility of red blood cells in sleep-apnea patients - (:unkn) unknown (ELSEVIER SCIENCE BV, 2003)
Background: Obstructive sleep apnea (OSA) refers to the occurrence of episodes of complete or partial pharyngeal obstruction with oxyhemoglobin desaturation during sleep. These hypoxia/reoxygenation episodes may cause generation of reactive oxygen species. Reactive oxygen species are toxic to biomembranes and may lead to the peroxidation of lipids. We tested the hypothesis that obstructive sleep apnea is linked to increased oxidative stress and lipid peroxidation. In order to identify target tissue/cell damage, we studied the osmotic fragility of red blood cells. Methods: Six subjects polysomnographically diagnosed as obstructive sleep apnea syndrome and 10 controls were included. After all subjects gave written informed consent, blood samples were collected in the morning between 08:00 and 09:00 a.m. following polysomnography. Blood samples were immediately transferred to the laboratory. Glutathione, lipid peroxidation and osmotic fragility of red blood cells were measured manually. Results: Mean glutathione and lipid peroxidation concentrations of patients were not different than those of control subjects (105.6 +/- 38.6 U/g Hb and 3.1 +/- 2.3 nmol MDA/l vs. 100.6 +/- 62.1 U/g Hb and 3.2 +/- 2.8 nmol MDA/l, respectively). In both groups, osmotic fragility of red blood cells was not changed. Conclusion: The present study failed to support the hypothesis that obstructive sleep apnea is linked with increased oxidative stress and lipid peroxidation. (C) 2003 Elsevier Science B.V. All rights reserved.
Keywords: sleep apnea; lipid peroxidation; osmotic fragility; glutathione; GAMMA-GLUTAMYLCYSTEINE SYNTHETASE; PARKINSONS-DISEASE; HUMAN-ERYTHROCYTES; OXIDATIVE STRESS; GLUTATHIONE; SUSCEPTIBILITY; HYDROPEROXIDE; EXPOSURE; ADDUCTS; DAMAGE